Chemistry, pharmacology and analysis of Pseudostellaria heterophylla: a mini-review - De-jun Hu; Farid Shakerian; Jing Zhao; Shao-Ping Li (BMC, 2019)
Abstract Pseudostellaria heterophylla is one of the well-known traditional Chinese medicines and has been used in clinics for 100 years in China. The chemistry and pharmacology of P. heterophylla were reviewed to understand its active compounds. Then analysis of these compounds related to quality control of this herb was discussed. For the analysis of chemicals, three aspects have been discussed in this review. The first two aspects focused on the methodologies for analysis of cyclic peptides and carbohydrates in P. heterophylla, respectively. The last one dealt with the other methods used for identification of P. heterophylla. Some rich chemicals such as oligosaccharides in this plant were rarely evaluated. Many analyses were performed on this plant, however, few of them were accepted as quality control method.